ATTITUDE OF ADOLESCENTS TOWARDS ALCOHOL & DRUGS IN RELATION TO THEIR FAMILY ENVIRONMENT - Dr. Rajvir Singh; Mangat Ram (Universal Research Reports, 2019)
Family is an organization in which members are connected by blood relations, it helps an individual to develop in every aspect of life and its reflection can be seen directly or indirectly in the form of socio-cultural and socio-economic bases. Families are involved in many practices and these may influence the personality of a child. Alcohol and drug consumption is a big crisis in society so the family environment is affected by abuse of substances. In the present study, 240 senior secondary school students of Sirsa District in Haryana were selected as a sample. It was found that the level of family environment was varying among adolescents and spread in high, moderate and low levels. It was found that the ‘Family Environment of Adolescents’ was significantly varied in Components of Family Environment on gender basis. No significant differences in ‘Expressiveness’, ‘Organization’ and ‘Control’ Components was found, but there exist significant differences in ‘Cohesion’, ‘Conflict’, ‘Acceptance and Caring’, ‘Active Recreational Orientation’ and ‘Independence’ Components of Family Environment among adolescents w.r.t. gender. A mild negative relationship of Cohesion, Expressiveness, Acceptance and Caring, Active Recreational Orientation and Independence Components of Family Environment with Attitude of Adolescents towards Alcohol and Drugs was found; whereas a moderate positive relationship of Conflict Components of Family Environment was found with Attitude of Adolescents towards Alcohol and Drugs. The findings of this study are supportive to some studies, so it is suggested to conduct more research in this area.